PENGEMBANGAN TES REPRESENTASI MATEMATIS DENGAN ANALISIS RASCH MODEL PADA SISWA SMP - Fahrurrazi, Fahrurrazi; Tandililing, Edy; Jamiah, Yulis (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to develop a mathematical representation test by analyzing the Rasch model and explaining the mathematical representation ability of junior high school students in Pontianak. This research is in the form of research and development with the type of research is the development instrument. The representation test was developed through the formative research stage, which is the preliminary stage; the preparation and design phase, then followed by the formative evaluation stage; one-to-one, expert review, small group with Rasch model analysis, and field tests. Based on the results of the item analysis, it was found that the mathematical representation test instrument analyzed by the Rasch model was precisely in accordance with the specified criteria, so that it could be used to measure students' mathematical representation abilities. Based on the results of the analysis of the answers, it was found that the mathematical representation of junior high school students in Pontianak mostly had difficulty in translating forms of image representation into verbal representations and translating forms of verbal representations into image representations.Â Keywords: Instruments Development, Representation Test, Analysis Of The Rasch ModelÂ